Mangrove vegetation and bird communities around Tegal Port, Central Java, Indonesia - Slamet Isworo; POERNA SRI OETARI (Society for Indonesian Biodiversity, 2020)
Abstract. Isworo S, Oetari PS. 2020. Mangrove vegetation and bird communities around Tegal Port, Central Java, Indonesia. Biodiversitas 21: 1551-1560. The ecological balance in Tegal harbor area needs to get serious attention due to the impacts of Tegal Port activities. For this purpose, the diversity of mangrove and avifauna (bird) can be used as bio-indicators of the ecological stability of the area. This study aimed to assess and analyze the diversity of plants and avifauna (birds) that live in mangrove and coastal zones around Tegal Port development area. Data collection was conducted using purposive random sampling method on two sites for vegetation and three sites for avifauna. The importance value index, Shannon-Wiener diversity index and Sorensen’s similarity index was calculated for the vegetation. For birds, we calculated the diversity and similarity index as well as identified their conservation status based on the IUCN Red List, CITES and government regulations. In terms of vegetation, Rhizophora mucronata and Avicennia marina dominate Site 2 (Tegalsari) while Casuarina equisetifolia and R. mucronata dominate Site 3 (Alam Indah Beach). Overall, the vegetation has low biodiversity index and similarity between sites is also low. For bird, there are 37 species from 18 families. Site 1 (Muara Reja) has the highest number of species with 29 species, followed by Site 2 (Tegalsari) with 25 species, and Site 3 (Alam Indah Beach) with 22 species. The three sites have moderate diversity index and there is high similarity index between sites. All bird species found in the study sites are listed as Least Concern under IUCN Red List, while there are two species protected under national protection law, i.e. Ardea alba and Glareola maldivarum. In general, the condition of mangrove vegetation around Tegal Port has low diversity. This suggests that the pressure on the environment is quite high, causing only few plant species to be able to live and dominate the ecosystem. The limited vegetation also causes birds community, especially the protected A. alba and G. maldivarum in Site 2, becomes increasingly difficult to find, because places to find food, breeding places and places to rest are disturbed.